Region- and Activity-Dependent Regulation of Extracellular Glutamate - Pinky, Nawrin F. (J Neurosci, 2018)
Transporter-mediated glutamate uptake plays an essential role in shaping synaptic neurotransmission. The rapid removal of synaptically released glutamate ensures the high temporal dynamics characteristic of fast excitatory chemical neurotransmission and prevents the overexcitation of extrasynaptic NMDA receptors that have been implicated in synaptic plasticity impairments and cell death. Despite clear regional differences in plasticity and excitotoxic thresholds, few studies have compared extracellular glutamate dynamics across different brain regions and in response to a range of neural activity including plasticity-inducing stimuli. Here, we used the rapid extracellular fluorescent glutamate sensor iGluSnFR (intensity-based glutamate-sensing fluorescent reporter) and high-speed imaging (205 frames per second) to quantify relative differences in glutamate clearance rates over a wide range of presynaptic activity in situ in the hippocampus, cortex, and striatum of male C57/BL6NCrl mice. We found that the hippocampus was significantly more efficient than the cortex and striatum at clearing synaptically released glutamate and that this efficiency could be attributed, at least in part, to faster glutamate diffusion away from the release site. In addition, we found that pharmacological inhibition of GLT-1, the brain's most abundant glutamate transporter, slowed clearance rates to only a fraction (∼20–25%) of the effect induced by nonselective transporter blockade, regardless of the brain region and the duration of presynaptic activity. In all, our data reveal clear regional differences in glutamate dynamics after neural activity and suggest that non-GLT-1 transporters can make a large contribution to the rate of glutamate clearance in the hippocampus, cortex, and striatum. SIGNIFICANCE STATEMENT Glutamate is the brain's most abundant neurotransmitter, and although essential for rapid cell–cell communication, too much glutamate can negatively impact cellular health. Extracellular glutamate levels are tightly regulated by membrane-bound transporters that rapidly remove the glutamate that is released during neural activity, thereby shaping both the spatial and temporal dynamics of excitatory neurotransmission. Using high-speed imaging of an optical sensor of extracellular glutamate, we show that glutamate dynamics vary widely from one brain region to the next and are highly dependent on the duration of synaptic activity. Our data demonstrate the heterogeneous nature of glutamate regulation in the brain and suggest that such regional differences can dramatically affect both the localization and duration of postsynaptic receptor activation during synaptic neurotransmission.